Watching Textual Screens Then and Now: Text Movies, Electronic Literature, and the Continuum of Countertextual Practice. Issue 2 (August 2016) - Wingate, Steven
Abstract : Contemporary works of electronic literature that focus on the use of moving text are aesthetically related to the text movies that arose in the experimental film community, particularly in the 1960s, and both share much in common with concrete and visual poetry. Though criticism has traditionally placed a barrier between works of electronic literature and cinematic text movies on the basis of their perceived medium (cinema characterised by emulsion and electronic literature characterised by computer code), textual screen works originating from both media utilise similar techniques in the presentation and manipulation of text. Interactivity is potentially a differentiator between electronic literature and cinema, but this distinction is negated by the fact that not all works of electronic literature are interactive (that is, they do not require an interactor in order to function). The increasing digitisation and, to a lesser extent, interactivity of cinema also argues against placing a gap between electronic literature and cinematic works that utilise the textual screen. Text movies, visual poetry, and other digital works featuring moving text can be seen as belonging to the same family; they are united by the aesthetic experience of perceiving them, which derives from a dynamic tension between the act of reading and the act of watching. Taken together, they form a continuum of countertextual practice that involves the destabilisation of reading and the displacement of literary significance away from traditional means of sense-making and towards the use of text-as-objects that do not always achieve the status of language.